Converged communication method of multi-source data about underground equipment based on internet of things. (14th December 2022) - Wu, Shunli; An, Haoping; Gao, Yan; Wang, Jianye; Su, Zhan
The difference and incompatibility of multi-source data in complex environment lead to high bit error rate and low efficiency in communication of downhole equipment. Therefore, a multi-source data fusion communication method for underground equipment based on internet of things is proposed. Using multi-dimensional information acquisition system, the feature recognition model of multi-source data of underground equipment is established. According to the distribution of boundary mesh objects among clusters, the boundary object set of data distribution is obtained, and the data features are extracted. The balance degree of multi-source data is calculated, and the data is represented in grid form to realise fusion. The communication process is optimised according to the convergence result. Experimental results show that the proposed method has high efficiency (the highest efficiency is 97%) and low bit error rate (the lowest bit error rate is 0), which improves the efficiency of multi-source data fusion of downhole equipment.